2009
DOI: 10.1111/j.1468-1331.2008.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study and PLA2G6 mutation screening analysis in Chinese patients with infantile neuroaxonal dystrophy

Abstract: The nine novel mutations identified in this study suggest the uniqueness of the PLA2G6 mutation spectrum in Chinese patients, and greatly extends the spectrum of known mutations in INAD patients. In addition to pathological evidence, genetic analysis can inform definitive diagnosis of INAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 15 publications
(40 reference statements)
3
57
0
Order By: Relevance
“…To date different types of sequence variations have been documented, including non-sense and missense mutations, small exons deletions, splice-site, and copy number variations (Morgan et al, 2006; Wu et al, 2009a; Crompton et al, 2010). Even though no clear genotype/phenotype correlation exists, the early onset and more aggressive forms are associated with two null mutations, while the atypical presentation is more common in individuals carrying missense mutations.…”
Section: Nbia Caused By Defects In Genes Coding For Proteins Involvedmentioning
confidence: 99%
“…To date different types of sequence variations have been documented, including non-sense and missense mutations, small exons deletions, splice-site, and copy number variations (Morgan et al, 2006; Wu et al, 2009a; Crompton et al, 2010). Even though no clear genotype/phenotype correlation exists, the early onset and more aggressive forms are associated with two null mutations, while the atypical presentation is more common in individuals carrying missense mutations.…”
Section: Nbia Caused By Defects In Genes Coding For Proteins Involvedmentioning
confidence: 99%
“…This indicates that the absence of cerebellar cortex signal hyperintensity does not rule out an INAD diagnosis (13). (2,6,(12)(13)(14)(15)(16)(17). In China, only 2 studies reported PLA2G6-associated neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In China, only 2 studies reported PLA2G6-associated neurodegeneration. The first study discussed 10 patients with INAD, who had been diagnosed through neuropathology, that were analyzed for PLA2G6 mutations (17). The second was a follow-up study of 25 Chinese children with PLA2G6-associated neurodegeneration that found 27 different mutations, of which 13 were novel (18).…”
Section: Discussionmentioning
confidence: 99%
“…Sural nerve biopsy has a good yield but usually requires availability of electron microscopy for ultrastructural analysis. The yield from muscle biopsy appears to be low [1,4]. Spheroids are not specific to INAD and may occur in PKAN and in various ill-defined chronic non-progressive or progressive neurological disorders [5].…”
Section: Neuropathological Findingsmentioning
confidence: 99%
“…It was suggested that there was protein misfolding and aggregation causing age-dependent impairment of axonal membrane homeostasis and protein degradation pathways, leading to progressive neurological deterioration [8]. Arachidonic acid toxicity may also play a role by increasing apoptosis [4].…”
Section: Animal Modelsmentioning
confidence: 99%